INTEGRITAS AKADEMIK DALAM PEMBELAJARAN BERBASIS GOOGLE CLASSROOM PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ASAHAN - Dailami Dailami; Sri Rahmayanti; Dian Armanto; Lanna Reni Gustianty (Smart Education, 2026)
Abstract: This study examines the level of academic integrity among students of the Faculty of Economics, Universitas Asahan, in Google Classroom (GCR)-based learning, with a focus on educational communication analysis. Using a cluster-based questionnaire administered to 55 students from the Management and Digital Business study programs, four clusters were measured: (1) perceived supervision and verification of GCR-based assignments, (2) academic dishonesty behavior and tendencies, (3) social and academic pressure in assignment submission, and (4) perceptions of sanctions and enforcement. The overall mean score of 3.18 falls in the moderate category. Cluster 4 (sanctions and enforcement, mean = 3.89) scored highest, followed by Cluster 1 (supervision and verification, mean = 3.64), Cluster 2 (dishonesty behavior, mean = 2.61), and Cluster 3 (social pressure, mean = 2.57). The findings indicate that external control mechanisms play a more dominant role in shaping student compliance with academic integrity norms than internal resistance to peer pressure, and that self-report measures of dishonesty are likely affected by social desirability bias. These results imply that strengthening academic integrity in GCR-based learning requires not only technical supervision and consistent sanction enforcement, but also deliberate cultivation of an honest academic culture at the classroom level. Keywords: Academic Integrity; Google Classroom; Educational Communication; Academic Dishonesty; Higher Education Abstrak: Penelitian ini bertujuan menganalisis tingkat integritas akademik mahasiswa Fakultas Ekonomi Universitas Asahan dalam pembelajaran berbasis Google Classroom (GCR), dengan fokus pada isu analisis komunikasi pendidikan. Menggunakan kuesioner berbasis klaster yang melibatkan 55 mahasiswa dari Program Studi Manajemen dan Bisnis Digital, penelitian ini mengukur empat klaster: (1) persepsi pengawasan dan verifikasi tugas berbasis GCR, (2) perilaku dan kecenderungan ketidakjujuran akademik, (3) tekanan sosial dan akademik dalam pengumpulan tugas, dan (4) persepsi terhadap sanksi dan penegakan aturan. Skor rata-rata keseluruhan sebesar 3,18 berada pada kategori sedang. Klaster 4 (sanksi dan penegakan aturan, mean = 3,89) memperoleh skor tertinggi, diikuti Klaster 1 (pengawasan dan verifikasi, mean = 3,64), Klaster 2 (perilaku ketidakjujuran, mean = 2,61), dan Klaster 3 (tekanan sosial, mean = 2,57). Temuan menunjukkan bahwa mekanisme kontrol eksternal berperan lebih dominan dalam membentuk kepatuhan mahasiswa terhadap norma integritas akademik dibandingkan ketahanan internal terhadap tekanan sebaya, dan bahwa pengukuran ketidakjujuran melalui self-report kemungkinan dipengaruhi oleh social desirability bias. Hasil ini mengimplikasikan bahwa penguatan integritas akademik pada pembelajaran berbasis GCR memerlukan tidak hanya pengawasan teknis dan penegakan sanksi yang konsisten, tetapi juga pembentukan budaya akademik jujur secara sengaja di tingkat kelas. Kata kunci: Integritas Akademik; Google Classroom; Komunikasi Pendidikan; Ketidakjujuran Akademik; Pendidikan Tinggi